Common coincidence and fixed points for several functions in b-metric spaces - Jayesh Tiwari; Dileep Kumar Sharma (Journal of Hyperstructures, 2023)
The purpose of this research paper is to show the existence and uniqueness of coincidence and fixed points for more then two functions on new contraction mapping and expansive mapping in b-metric spaces. Also we give several corollaries in such spaces. These results are extend many of the past results and will help to research scholar in their advance works.